Design of a web-based project planning system using the Laravel framework at PT. Globalindo Lestari Utama - Sahrial; Heni Wulandari; Irwan; Dedi Gunawan (Journal of Information Technology, computer science and Electrical Engineering, 2024)
PT. Globalindo Lestari Utama is a technology startup company engaged in information and communication. As a growing startup, PT. Globalindo Lestari Utama requires an effective project management system to overcome various challenges such as difficulty in monitoring work progress, unstructured task delegation, and unclear work estimate recording. In addition, reporting via WhatsApp groups is often missed because it is mixed with other chats, thus hampering the efficiency of project monitoring. This study aims to design and implement a web-based project planning system using the Laravel framework. This system is designed to provide features for monitoring work progress, managing and assigning structured tasks, and recording accurate work estimates. The project manager will create project data, then delegate tasks to the lead developer. The leader will break down these tasks and delegate them again to the developers. The method used in this study is the Waterfall model, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The Laravel framework was chosen because of its ability to provide a strong structure, security, and ease in developing web applications. The implementation of this system aims to improve the efficiency of project management and ensure that project reports and updates are no longer missed in group chats. The results of the implementation show a significant increase in the efficiency of project management at PT. Globalindo Lestari Utama. This system allows project managers and leader developers to document, manage, and delegate tasks more effectively. The conclusion of this study is that a web-based project planning system using the Laravel framework can overcome project management problems at PT. Globalindo Lestari Utama and improve the company's overall performance.